2006
DOI: 10.1051/0004-6361:20053073
|View full text |Cite
|
Sign up to set email alerts
|

Precise radial velocities with BOES

Abstract: We present the first results from a high-precision radial velocity study of the K2 III giant star α Ari. Observations were acquired over 6 nights in 2004 using the new high-resolution spectrograph BOES (Bohyunsan Observatory Echelle Spectrograph) of the 1.8-m telescope. A high radial-velocity precision was achieved by using the high-resolution (R = 90 000) mode of BOES and an iodine gas absorption cell. The radial velocity measurements made during JD = 2 452 948−2 452 950 show coherent, low-amplitude variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…We also confirmed the short-period oscillations previously found in α Ari (Kim et al 2006). We found no evidence of the correlation between the 381 day RV variation and the EWs of H α lines or the Hipparcos photometry.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also confirmed the short-period oscillations previously found in α Ari (Kim et al 2006). We found no evidence of the correlation between the 381 day RV variation and the EWs of H α lines or the Hipparcos photometry.…”
Section: Discussionsupporting
confidence: 90%
“…In previous publication, we (Kim et al 2006) reported multiperiodic oscillations in α Ari with periods P 1 = 0.571 day (or aliases at 0.445 or 0.871 days) observed during November to December 2003. The average amplitude variation ranges ∼±20 m s −1 just overnight.…”
Section: Introductionmentioning
confidence: 72%
“…Results from the first 3 years of our survey show that the majority (more than 90%) of our sample of K-giants show RV dariations. Among them, we found spectroscopic binaries, pulsating variables (see Kim et al 2006), and several periodic RV variable stars. Our survey confirmed an exoplanet around β Gem (Han et al 2008) discovered by Hatzes et al (2006) and Reffert et al (2006).…”
Section: Introductionmentioning
confidence: 92%
“…We have reported two new exoplanets (Han et al 2010;Lee et al 2011) and confirmed an exoplanet ) and an oscillating star (Kim et al 2006).…”
Section: Observations and Analysismentioning
confidence: 57%
“…We solved the matrix equation using singular value decomposition instead of the maximum entropy method adopted by Endl et al (2000). The code has been used in several cases (Kim et al 2006;Han et al 2008Han et al , 2010Lee et al 2008Lee et al , 2011.…”
Section: Observations and Analysismentioning
confidence: 99%